Reservoirs: mirrors of the surrounding landscape? - Geraldes, Ana Maria (2010)
To assess in what extent the environmental quality of aquatic systems reflect landscape features several water quality parameters were determined in two reservoirs. Concomitantly, the surrounding landscape was characterized and the existing potential sources of phosphorous and nitrogen runoff were identified and when possible estimated. Located in a mountainous area with negligible direct human influence, it was expected to find lower amounts of suspended organic matter and nutrients in Serra Serrada Reservoir. Water level fluctuations caused by intensive human water use, grazing and frequent land fires in the surrounding landscape can explain the unexpected high values of the mentioned parameters. In Azibo Reservoir the factors with greatest influence on water parameters seem to be allochthonous sources of nutrients originated from agriculture and grazing in the catchment area and recreational activities. However, in this particular case the potential sources of nutrients could have been minimized by the patchy structure of the surrounding landscape.